Use of the PK Papyrus covered coronary stent in the treatment of Kawasaki disease‐associated giant coronary artery aneurysms. Issue 7 (26th October 2022) - Naimi, Iman; Morray, Brian; Portman, Michael A.; Steinberg, Zachary L.
Abstract: Kawasaki disease (KD) is an acute vasculitis that can cause coronary artery inflammation and aneurysm formation leading to early obstructive disease. We describe the use of PK Papyrus covered stents (Biotronic, Inc.) in three pediatric patients to exclude coronary artery aneurysms (CAA) from the circulation and relieve aneurysm associated stenoses. Follow‐up angiography at 11–17 months postprocedure demonstrated persistent exclusion of CAA and varying degrees of in‐stent restenosis (ISR). Two patients required percutaneous coronary intervention with drug eluting stent (DES) implantation to relieve in‐stent stenosis. Our findings suggest that CAA exclusion with the PK Papyrus stent is possible and may be a valuable tool in simultaneously treating stenotic and thrombogenic CAA in pediatric KD patients. ISR of these non‐DES remains an issue and may require additional interventions within the short‐term to maintain vessel patency.